Monocytes from preeclamptic women previously treated with silibinin attenuate oxidative stress in human endothelial cells - Gomes, Virgínia Juliani [UNESP]; Rezeck Nunes, Priscila [UNESP]; Haworth, Sarah McCann; Sandrim, Valéria Cristina [UNESP]; Peraçoli, José Carlos [UNESP]; Peraçoli, Maria Terezinha S. [UNESP]; Carlström, Mattias (Taylor & Francis, 2021)
Objective: To investigate whether the supernatant from monocytes of preeclamptic and normotensive pregnant women, cultured in vitro with silibinin, can modulate oxidative stress in HUVEC. Methods: Concentrations of IL-1β, IL-10, and TNF-α in monocyte culture supernatants were determined by ELISA. HUVEC and their supernatant cultures were employed for determination of NO, nitrite and nitrate, lipid peroxidation, and hemeoxygenase-1 (HO-1). Results: HUVEC treatment with supernatant of preeclamptic monocytes cultured with silibinin produced increased levels of nitrite, reduced lipid peroxidation, and increased HO-1. Conclusion: Supernatant of monocytes from preeclamptic women induce oxidative stress in HUVEC which can be reduced by silibinin treatment. Abbreviations: DAF-FMTM, Diaminofluorescein-FM; EDTA, Ethylenediaminetetraacetic acid; HO-1, heme oxygenase-1; HPLC, high-performance liquid chromatography; HUVEC, human umbilical vein endothelial cell; MDA, malondialdehyde; NO, nitric oxide; NT, normotensive; PE, preeclampsia; ROS, reactive oxygen species; Sb, silibinin.
Keywords: HUVEC; monocytes; oxidative stress; preeclampsia; silibinin